Do sound infrastructure governance and regulation affect productivity growth? New insights from firm level data - Demmou, Lilas (OECD Economics Department Working Papers, 2020)
Measuring the quality of governance and regulation in various ways and focusing on energy, transport and telecommunications, this paper shows that both sound governance of infrastructure investment and pro-competitive regulation in network industries are associated with stronger productivity growth in firms operating downstream